Reasons for part-time employment - Wojtkowiak, Grzegorz (Powody zatrudnienia w niepełnym wymiarze godzin, 2019)
The article deals with one of the symptoms of making work more flexible, i.e. part-time work. The reason for choosing such a problem is low part-time employment in Poland. The main goal is to answer the question: what can motivate and what actually motivates employees to work on a part-time basis. The text presents the issues in relation to other common and contemporary phenomena on the labor market, as well as the scale of part-time work using current statistical data. On the basis of own research conducted with the use of a survey in the group of professionally active women, the role of motives and identified advantages of part-time work were indicated
Management Forum, 2019, vol. 7, no. 1, s. 21-26
Keywords: flexibility; working time; sustainable development; flexicurity; work-life balance; elastyczność; czas pracy; zrównoważony rozwój